Distributed fiber optic interferometric geophone system based on draw tower gratings - Ruquan Xu (Photonic Sensors, 2017)
Abstract A distributed fiber optic interferometric geophone array based on draw tower grating (DTG) array is proposed. The DTG geophone array is made by the DTG array fabricated based on a near-contact exposure through a phase mask during the fiber drawing process. A distributed sensing system with 96 identical DTGs in an equal separation of 20 m and an unbalanced Michelson interferometer for vibration measurement has been experimentally validated compared with a moving-coil geophone. The experimental results indicate that the sensing system can linearly demodulate the phase shift. Compared with the moving coil geophone, the fiber optic sensing system based on DTG has higher signal-to-noise ratio at low frequency.